How does Women Entrepreneurship Matter to Financial Performance? Insights from Entrepreneurs Accessing Islamic Microfinance Services - Palasari, Rr. Suci; Yuniarti, Sari; Apriyanto, Gaguk; Subiantoro, Edi; Haryanto, Sugeng (Journal of Accounting Research, Organization and Economics, 2023)
Objective This research aims to analyze the influence of women's entrepreneurship orientation on financial performance. It specifically focuses on women entrepreneurs, acknowledging their proven significant contributions to society and the country through MSME businesses.Methodology This paper explores the potential for women's involvement in diverse productive activities through MSME businesses aimed at enhancing family welfare. The research focuses on entrepreneurs accessing microfinance services through the National Amil Zakat Agency (BAZNAS) Malang, Indonesia, encompassing a total of 250 MSMEs. The final sample consists of 153 women entrepreneurs. The study employs a descriptive quantitative approach, utilizing questionnaires and annual financial reports. Partial Least Squares (PLS) analysis is conducted using the Smart-PLS program.Results The findings highlight the significance of womens entrepreneurship orientation in driving the financial performance of MSMEs. This study also indicated that indicators of women's entrepreneurship orientation that significantly contribute to financial performance include internal locus of control, characteristics of a womens entrepreneur having high initiative. Second, the need for achievement is represented by a characteristic of a woman entrepreneur who can contribute to better performance. Third, self-reliance is represented by the characteristics of a womens entrepreneur able to be responsible in running her business. Lastly, extroversion is represented with characteristics of an energetic womens entrepreneur are full of enthusiasm in running her business. It emphasizes the positive impact that such orientation can have on the financial outcomes of microenterprises, particularly when considering the business tenure they have been operating.Research limitations/implications This research collected data from various types and levels of business sectors, making it less focused. Additionally, the respondents were only those residing in the city of Malang, while BAZNAS has a broader geographical coverage.Novelty/Originality This implies that women's entrepreneurship orientation is crucial for the growth of microbusiness practitioners. Notably, those with a strong entrepreneurial mindset usually achieve good financial performance.